Strategi Pelayanan Three In One Pada Kantor Kelurahan Nusa Indah Kota Bengkulu - Yusuarsono, Yusuarsono; Sariningsih, Marida; Puspita, Febiola Diah (Jurnal Multidisiplin Dehasen (MUDE), 2024)
This study aims to analyze the Three In One service strategy at the Nusa Indah Sub-District Office, Bengkulu City, which provides a bundled administrative service for birth certificates, family cards, and child identity cards. The research adopts a descriptive qualitative approach using SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) based on Rangkuti’s framework (2011). Data were collected through in-depth interviews, direct observation, and documentation involving local government staff and community members as informants. The results indicate that the service’s strength lies in its human resources, who are well-aligned with their competencies, and the use of simple technologies like WhatsApp groups to expedite communication. However, weaknesses include inadequate facilities, lack of modern technological equipment, and limited financial resources. Opportunities are enhanced by local government policies that provide free and integrated death certificate administration services. The main threats arise from the public’s low awareness of required documents and limited staff responsiveness during peak service hours. The study recommends upgrading technology-based facilities and providing intensive training for staff to improve the overall quality of public services.